ChatGPT in Language Learning: Opportunities, Challenges, and Future Directions - Oliinyk, Olga (ХДАК, 2024)
As with technological innovations (Google Translate, language apps, and voice assistants), ChatGPT is able to develop authentic language skills. ChatGPT offers interactive, real-time feedback, making it a valuable tool for second-language acquisition. By simulating real conversations, ChatGPT helps learners practice speaking, correct grammar mistakes, and build vocabulary in a low-pressure environment. This is useful for adults learning English as a second language. Teachers can also use ChatGPT to develop customized quizzes, generate reading materials, and simulate practical communication scenarios. These applications help reinforce grammatical structures and foster fluency through practice. ChatGPT can support flipped classrooms, where learners engage with online content before class and spend face-to-face time practicing conversational skills. ChatGPT opens new pathways for personalized and dynamic language learning, making practice more accessible for learners of all levels.
Keywords: штучний інтелект в освіті; вивчення іноземних мов